Social Interaction Model Of Different Religious Communities In The Karo District, Northern Sumatera - Sahrul, Sahrul; Daulai, Afrahul Fadhila (Program Studi Pengembangan Masyarakat Islam, 2024)
This study observes social interaction models of different religious communities in Karo District, Sumatera Utara. This area is classified as a plurality in terms of religion, ethnicity, class and culture. A qualitative research is employed which data is obtained from interviews, observations and documentary studies. Data analysis techniques using data reduction, data display and verification refer to the opinion of Miles and Huberman. The results found that five social interaction models of different religious. First, Community's Social interactions between local governments and Muslim minority's social. Second, interaction between religions and different religions. Third, social interactions of Muslim and non-Muslim families. Fourth, social interaction between neighbors and neighborsliness. Finally, social interaction between mosque worshipers and church worshipers. From the five social interaction models, it is concluded that people of different religions will be harmonious and respectful each other.